AS-SHARIA MAQASHID REVIEW OF MARRIAGE AGE LIMIT IN LAW NUMBER 16 YEAR 2019 - Al Kautsar, Muhammad Syakir; Miswanto; Mu'in, Fathul (Al-Mizan (e-Journal), 2022)
This article discusses the age limit for marriage based on the maqasid al-sharia perspective in marriage law. This research is library research with the main data source being Law Number 16 of 2019. The data that has been collected is then analyzed using qualitative descriptive methods. The results of the study indicate that although there is no clear text that regulates the minimum age for marriage, the presence of a revision of Law Number 16 of 2019 concerning Marriage which regulates the minimum age for marriage is not contrary to the spirit of Islamic law, because the regulation is an effort from the government. to encourage the realization of the purpose of marriage, namely creating a serenity family, love, and affection. In addition, the regulation is also under the purpose of applying the law (maqasid as-sharia), namely hifz al-nasf (guarding the soul) and hifz al-nasl (guarding offspring).